Gambaran Kadar Glukosa dan Total Kolesterol pada Wanita Hamil di Kabupaten Bangli, Bali: An Overview of Glucose Levels and Total Cholesterol Levels among Pregnant Women in Bangli District, Bali - Heri Setiyo Bekti; Ni Nyoman Astika Dewi; Luh Putu Rinawati; Luh Ade Wilankrisna; I Made Suarjana; I Made Yogi Hardiyanta; Ni Putu Lisa Anjani; Aprilia Rakhmawati (Jurnal Bidan Cerdas, 2022)
Introduction: Gestational diabetes mellitus (GDM) is a state of glucose intolerance that was first detected during pregnancy. GDM is increasing worldwide, it is estimated that 15% to 22% of all pregnancies are affected by GDM. GDM can be associated with many consequences, such as fetal macrosomia, preeclampsia, and high caesarean rates. The purpose of this study was to determine the description of glucose and total cholesterol levels in pregnant women in Bangli Regency, Bali. Methods: This research method is descriptive by checking glucose and total cholesterol levels using the enzymatic-colorimetric method. The subjects in this study were 33 pregnant women, with sampling method using the probability sampling method, with a simple random sampling technique. Results: The result of this study is, glucose levels in all samples were in the normal category, while for total cholesterol levels 48,48% were in the normal category and 42,42% were in the abnormal category. Conclusion: Normal glucose levels can be caused by several factors such as the age of the respondent under 40 years, gestational age at term, and the hormones that regulate blood glucose in the body functioning properly. An increase in cholesterol levels can be caused by an increase in sexsteroid hormones, as well as changes in liver and adipose tissue metabolism. An increase in total cholesterol levels in pregnant women needs to be watched out for because it can be on of the markers of the incidence of GDM.   ABSTRAK Pendahuluan: Diabetes melitus gestasional (DMG) merupakan keadaan intoleransi glukosa yang pertama kali terdeteksi selama kehamilan. DMG meningkat di seluruh dunia, diperkirakan 15% sampai 22% dari semua kehamilan dipengaruhi oleh DMG. DMG dapat dikaitkan dengan banyak konsekuensi, seperti makrosomia janin, preeklampsia, dan tingkat operasi caesar yang tinggi. Tujuan dari penelitian ini adalah untuk mengetahui gambaran kadar glukosa sewaktu dan kolesterol total pada ibu hamil di Kabupaten Bangli, Bali. Metode: Metode penelitian ini adalah deskriptif dengan memeriksa kadar glukosa sewaktu dan kolesterol total menggunakan metode enzimatik kolorimetri. Subyek pada penelitain 33 ibu hamil, dengan cara penarikan sampel dengan mengunakan metode probality sampling, dengan teknik simple random sampling. Hasil: Hasil dari penelitian ini, diperoleh kadar glukosa sewaktu seluruh sampel berada pada kategori normal sedangkan untuk kadar kolesterol total sebanyak 48,48% berada pada kategori normal dan 42,42% pada kategori abnormal. Kesimpulan: Kadar glukosa yang normal dapat disebabkan oleh usia repsonden di bawah 40 tahun, usia kehamilan yang cukup bulan, dan hormon pengatur glukosa yang berfungsi dengan baik. Peningkatan kadar kolesterol total dapat disebabkan oleh peningkatan hormon steroid seks, perubahan metabolisme hati dan jaringan adipose. Peningkatan kadar kolesterol total pada ibu hamil perlu diwaspadai karena dapat menjadi salah satu penanda kejadian DMG.